Immunoglobulin fetal therapy and neonatal therapy with antiviral drugs improve neurological outcome of infants with symptomatic congenital cytomegalovirus infection. (February 2021) - Tanimura, Kenji; Shi, Yutoku; Uchida, Akiko; Uenaka, Mizuki; Imafuku, Hitomi; Ikuta, Toshihiko; Fujioka, Kazumichi; Morioka, Ichiro; Deguchi, Masashi; Minematsu, Toshio; Yamada, Hideto
Highlights: Symptomatic congenital CMV infection causes long-term sequelae in affected infants. Neonatal antiviral therapy can improve neurological outcomes of affected infants. Immunoglobulin fetal therapy may improve neurological outcomes of affected infants. Combination of fetal/neonatal therapy may be more effective than neonatal therapy only. Abstract: Infants with symptomatic congenital cytomegalovirus infection (cCMV) suffer from long-term sequelae. This study aimed at evaluating the efficacy of combining immunoglobulin (Ig) fetal therapy (FT) and neonatal therapy (NT) with antiviral drugs to improve neurological outcomes of affected infants. Women whose fetuses had symptomatic cCMV received Ig injection into the fetal peritoneal cavity and/or maternal blood as FT, while affected newborns received oral valganciclovir or intravenous ganciclovir as NT. We compared the neurological outcomes at ≥18 months old between infants receiving FT with or without NT (FT group) and those receiving NT only (NT group). From 2009–2019, 15 women whose fetuses had symptomatic cCMV received FT, while 19 newborns received NT only. In FT group, two newborns died, and two were <18 months old. Neurological outcomes of the remaining 11 infants in FT group were as follows: normal 45.5 %, mild impairments 36.4 %, and severe impairments 18.2 %. In NT group, one newborn died, one's parents refused the follow-up, one was <18 months old, and two had only chorioretinitis as symptoms. Neurological outcomes of the remaining 14 infants in NT group were as follows: normal 21.4 %, mild impairments 14.3 %, and severe impairments 64.3 %. The proportion of infants with severe impairments in FT group was significantly lower than that in NT group (18.2 % vs 64.3 %, p < 0.05). This is the first trial demonstrating that the combination of Ig FT and NT with antiviral drugs may be more effective in improving neurological outcomes of newborns with symptomatic cCMV as compared to NT only.